The Genetic Ancestry of Modern Indus Valley Populations from Northwest India - Pathak, Ajai K. (Am J Hum Genet, 2018)
The Indus Valley has been the backdrop for several historic and prehistoric population movements between South Asia and West Eurasia. However, the genetic structure of present-day populations from Northwest India is poorly characterized. Here we report new genome-wide genotype data for 45 modern individuals from four Northwest Indian populations, including the Ror, whose long-term occupation of the region can be traced back to the early Vedic scriptures. Our results suggest that although the genetic architecture of most Northwest Indian populations fits well on the broader North-South Indian genetic cline, culturally distinct groups such as the Ror stand out by being genetically more akin to populations living west of India; such populations include prehistorical and early historical ancient individuals from the Swat Valley near the Indus Valley. We argue that this affinity is more likely a result of genetic continuity since the Bronze Age migrations from the Steppe Belt than a result of recent admixture. The observed patterns of genetic relationships both with modern and ancient West Eurasians suggest that the Ror can be used as a proxy for a population descended from the Ancestral North Indian (ANI) population. Collectively, our results show that the Indus Valley populations are characterized by considerable genetic heterogeneity that has persisted over thousands of years.